2018
DOI: 10.11603/1681-2727.2018.2.9025
|View full text |Cite
|
Sign up to set email alerts
|

Діагностичне Значення Нейроспецифічних Маркерів Nse, S-100, Gfap, MBP І BDNF У Цереброспінальній Рідині Хворих На Вірусний Менінгіт

Abstract: Мета роботи – визначити діагностичну цінність рівнів нейроспецифічних маркерів NSE, GFAP, S–100, MBP та BDNF у ЦСР дорослих хворих на вірусні менінгіти.Пацієнти і методи. Для дослідження були залучені 50 пацієнтів з вірусними менінгітами віком від 18 до 65 років. Пацієнти з менінгітом, що викликаний вірусом простого герпесу 1,2, склали 1-у групу (n=21), з Епштейна-Барр менінгітом − 2-у групу (n=19), з ентеровірусним менінгітом – 3-ю групу дослідження (n=10). Рівень нейроспецифічних маркерів визначався у ЦСР хв… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Multiple studies involving EBV have shown that the virus infection could promote the expression of neurotropic growth factors such as brain-derived neurotropic factor (BDNF) and glial cell-derived neurotropic factor (GDNF) ( Ng et al, 2012 ; Jakhmola and Jha, 2021 ) in the infected cells. Clinical reports evaluating EBV meningoencephalitis/meningitis have corroborated the claim, as an increase in neurotropic factors was observed in the patient's CSF samples ( Chiaretti et al, 2014 ; Kozko et al, 2018 ).…”
Section: Understanding the Role Of Ebv In The Cell Cycle And Its Regu...mentioning
confidence: 61%
“…Multiple studies involving EBV have shown that the virus infection could promote the expression of neurotropic growth factors such as brain-derived neurotropic factor (BDNF) and glial cell-derived neurotropic factor (GDNF) ( Ng et al, 2012 ; Jakhmola and Jha, 2021 ) in the infected cells. Clinical reports evaluating EBV meningoencephalitis/meningitis have corroborated the claim, as an increase in neurotropic factors was observed in the patient's CSF samples ( Chiaretti et al, 2014 ; Kozko et al, 2018 ).…”
Section: Understanding the Role Of Ebv In The Cell Cycle And Its Regu...mentioning
confidence: 61%